(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. The article discusses the role of phraseological units with the mythological basis in culture and language. Their origin, functions and influence on the formation of the worldview of different nations are analyzed. Examples of the most famous expressions associated with the ancient Greek, Roman, Scandinavian and Slavic mythology are given. Particular attention is paid to the importance of such phraseological units in everyday speech, literature and other areas of communication.